The integrity and stability of specimens under different storage conditions for glucose-6-phosphate dehydrogenase deficiency screening using WST-8 - Chamchoy, K; Praoparotai, A; Pakparnich, P; Sudsumrit, S; Swangsri, T; Chamnanchanunt, S; Songdej, D; Imwong, M; Boonyuen, U (Elsevier, 2021)
Accurate measurement of glucose-6-phosphate dehydrogenase (G6PD) activity is critical for malaria treatment as misclassification of G6PD deficiency could cause serious harm to patients. G6PD activity should be assessed in blood samples on the day of collection. Otherwise, specimens should be stored under suitable conditions to prevent loss of G6PD activity. Here, we assessed stability and integrity of G6PD testing in samples from normal controls, heterozygous females, and G6PD deficient individuals using water-soluble tetrazolium salts (WST-8) assay. Specimens were stored as ethylenediaminetetraacetic acid (EDTA) whole blood and dried blood spots (DBS) at various temperatures (37 °C, room temperature, 4 °C and -20 °C) and under different humidity conditions (with and without desiccant). G6PD normal samples were stable for up to 1 year when stored at -20 °C under controlled conditions, with 85% and 91% G6PD activity in EDTA whole blood and DBS in the presence of desiccant, respectively. Specimens from heterozygous females showed greater G6PD activity when stored as DBS, with 85% enzyme activity after 1 year of storage at -20 °C under controlled conditions in the presence of desiccant. G6PD deficient samples rapidly lost enzyme activity in all storage conditions tested. However, the reduction in G6PD enzyme activity in G6PD deficient samples did not interfere with G6PD classification. Samples stored under suitable conditions for G6PD testing will allow accurate measurement of enzyme activity, prevent misclassification of G6PD deficiency and enable safe and effective use of antimalarial drugs such as primaquine and tafenoquine.